Akulturasi Praktik Keberagamaan Islam Dalam Tradisi Perang Timbung Di Desa Pejanggik Lombok Tengah - Nuruddin, Nuruddin; Nahar, Nur (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to examine comprehensively about the perang timbung tradition which has a goal as a repellent to balaq and an expression of gratitude to Allah SWT. In addition, the tradition marries Islamic values in it. The method used is a qualitative descriptive approach. Data collection techniques used are interviews, observation and documentation, then analyzed deductively and inductively. The theory used to analyze the data is the theory of symbolic interactionism, integration theory and social interaction theory. The results of the study illustrate that the acculturation of religious practices in the perang timbung tradition has long been preserved by the people of Pejanggik Village as a form of gratitude to Allah SWT. Acculturation that occurs between Islam and the tradition of mutual benefit and need, Islamic religious practice is a symbol of devotion and a form of worship to Allah, and tradition is something that is believed to have been left by the ancestors who have values embedded in society such as the value of friendship, the value of gratitude and the value of gotong royong.. Islamic religious practices carried out in the perang timbung tradition such as dhikr, recitation of berzanji and sermons and prayers.